Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1126/science.253.5020.637
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition at Crystal Interfaces

Abstract: Nucleation, growth, and dissolution of crystals have been studied by stereochemical approach involving molecular recognition at interfaces. A methodology is described for using ;;tailor-made'' additives designed to interact stereospecifically with crystal surfaces during growth and dissolution. This procedure was instrumental in controlling crystal morphology and in revising the concept of the structure and symmetry of solid solutions. Consequently, it was applied to the transformation of centrosymmetric singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
327
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 435 publications
(335 citation statements)
references
References 45 publications
(6 reference statements)
7
327
1
Order By: Relevance
“…Mann [31] states that this activation energy may also depend on the two-dimensional structure of different crystal faces, indicating that there is a variation in complementarity of various crystal faces and the organic substrate. Weissbuch et al [59] describe the auxiliary molecules which promote or inhibit crystal nucleation depending on their composition.…”
Section: Nucleationmentioning
confidence: 99%
“…Mann [31] states that this activation energy may also depend on the two-dimensional structure of different crystal faces, indicating that there is a variation in complementarity of various crystal faces and the organic substrate. Weissbuch et al [59] describe the auxiliary molecules which promote or inhibit crystal nucleation depending on their composition.…”
Section: Nucleationmentioning
confidence: 99%
“…The complexity of multiple conformations while dealing with pharmaceutically relevant molecules makes extension of such theories to pharmaceuticals rather difficult and may be the cause of limited progress in this area. While the advancement of supramolecular chemistry in disciplines such as ceramics, photography, and semiconductors has therefore been significant, the concept is still at its inception in pharmaceuticals and has only occasionally been reported [8,[10][11][12].This body of work is intended to serve as a proof of concept for the application of supramolecular chemistry in drug development. In particular, this work is designed to evaluate crystal doping by recrystallization from supercritical media.…”
Section: Introductionmentioning
confidence: 99%
“…79 Peptide selectivity is likely due to the recognition of a combination of chemical (hydrogen bonding, polarity, and charge effects) and structural (size and morphology) features. 80,81 Whaley et al 29 described a peptide that was specific not only to gallium arsenide over silicon, but bound the (100) crystal face over the (111)B. The specificity of another gold binding peptide, GBP1, was examine using a quartz-crystal microbalance and was found to preferentially absorb to gold over platinum and silica, and suggested that polar moieties and the physical conformation of the peptide itself may play a role in the binding preference to gold over platinum or silica.…”
Section: Selectivity Of Gold-binding Peptidesmentioning
confidence: 99%